(untitled) (KULT_online, 2013)
The latest monograph by German Romance scholar Ottmar Ette examines the mutual intertwining of literary history and the different phases of globalization from the Early Modern Age to the present from a motion-oriented perspective. It pursues the question of which continuities and discontinuities have shaped the – real and imagined – global movement patterns in "vier Phasen beschleunigter Globalisierung" (p. 7). Moreover, it analyses the persistence of some of these choreographies in contemporary global phenomena. Based on the fundamental hypothesis that the unique characteristics of literature have always been its both transareal and transcultural genesis and scope of effect, this volume investigates dynamic global spaces of motion and the enactment of their multiple logics in various literary and media genres. Thus, TransArea unfolds a complex panorama of global histories of motion, the "polylogic" (S. 5) of which is described accurately and correlated in multiple ways.